2019
DOI: 10.1063/1.5125992
|View full text |Cite
|
Sign up to set email alerts
|

Deformation-stimulated Ex luminescence in a RbI single crystal

Abstract: Using X-ray luminescence spectra, the enhancement of both σ-luminescence of self-trapped excitons and Ех luminescence (band maxima at 3.89 and 3.1 eV, respectively) has been revealed for the first time in RbI single crystals exposed to elastic uniaxial stress at 93 K. The intensity of these emissions increases linearly with the relative degree of applied uniaxial deformation of the crystal up to ɛ = 1%, while the luminescence undergoes saturation at higher values of ɛ. The behavior of the I = f (ɛ) dependence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…Based on the correlated increase in the intensity of E x -and σ -luminescence with a decrease in the symmetry of the lattice of RbI crystal, it is concluded that the nature of E x -luminescence is not associated with the participation of sodium impurity, as many researchers assumed [8][9]21]. The experimental results obtained in [16] allow us to assume that their E x -luminescence corresponds to the radiative decay of STEs, which has its own nature in RbI crystal.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Based on the correlated increase in the intensity of E x -and σ -luminescence with a decrease in the symmetry of the lattice of RbI crystal, it is concluded that the nature of E x -luminescence is not associated with the participation of sodium impurity, as many researchers assumed [8][9]21]. The experimental results obtained in [16] allow us to assume that their E x -luminescence corresponds to the radiative decay of STEs, which has its own nature in RbI crystal.…”
Section: Resultsmentioning
confidence: 92%
“…The boundary of elastic and plastic deformation is determined experimentally by the linear section of the dependence of the intensity of σ -and E xluminescence on the degree of deformation at which Hooke's law is valid [16]. In this regard, to create only the elastic part of the deformation, the crystals were deformed at low temperature (85 K) within the range of ε = 0.8 − 1.0% in a special cryostat under high technical vacuum conditions [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…На приведенном на рис. 5 спектре интенсивная полоса поглощения в районе 7−8 µm вызвана примесью бария (Ba), введенной специально для улучшения сцинтилляционных свойств кристалла, которая не влияет на пропускание кристалла в других областях [28,30,31].…”
Section: результаты эксперимента и обсуждениеunclassified
“…This leads to a change in the electrical [4,5] and optical characteristics [3,[6][7][8] of the materials under study. In particular, the motion of dislocations that occurs during PD [9,10] changes the immediate environment of luminescence centers and affects the mechanisms of excitation energy transfer, which in turn causes a change in the luminescent properties of deformable materials [11][12][13].…”
Section: Introductionmentioning
confidence: 99%